BENTUK DAN FUNGSI MITOS LEGENDA SELOKAJANG BAGI MASYARAKAT DESA SELOKAJANG KECAMATAN SRENGAT KABUPATEN BLITAR - GAYUH ELPANUSI, GAYUH ELPANUSI; Sulistyorini , Dwi (Hasta Wiyata, 2024)
People's belief in forbidden myths and legendary myths is still believed today and is still passed down from generation to generation. This research aims to describe the form and function of the Selokajang legend myth for the people of Selokajang Village, Blitar Regency. This type of research is qualitative research that uses descriptive methods. The theory used in this research is the theory of the Endraswara form which includes the sirikan (ban) myth and the legendary myth. Kirk's theory of myth functions includes entertaining and explanatory functions. The results of this research show that the myths in Selokajang Village are generally sirikan (ban) myths which are related to the legend of Selokajang Village. The legend of Selokajang Village is also indirectly a mythical legend. This is because the mythical legend is a public belief in important events regarding the origins or history of the formation of Selokajang Village